Stakeholders Engagement on Effective Implementation of Focusing Resources on Effective School Health (FRESH) Initiative in Nigeria - OWOLABI, Habeeb; AYOADE, Timothy; ADESOLA, Barakat; ADENIYI, Adetola (Ilorin Journal of Education, 2024)
Focusing Resources on Effective Stakeholders Engagement (FRESH) framework serves as a comprehensive guide to improving health outcomes among school-going children. In Nigeria, the successful execution of FRESH relies significantly on robust stakeholder engagement strategies. The School Health Programme is a comprehensive initiative addressing the well-being of both students and staff within educational settings. The emergence of the FRESH approach, born out of the World Education Forum in Dakar in April 2000, aimed to fulfill these components. However, Nigeria, as a developing nation, faces challenges in realizing these objectives. This article identified and addressed the existing gaps hindering the implementation of the FRESH approach in schools. By delving into the Background of School Health Programmes in Nigeria and the FRESH Approach, it sheds light on the vital components of the School Health Programme and the specific objectives outlined by FRESH. Furthermore, this article outlined strategies and approaches for effectively integrating the FRESH approach into the school system. Recommendations include stakeholder involvement, advocating for Ministries and Government agencies at all levels to define and enforce their roles in implementing the School Health Programme, organizing awareness programs for school administrators, teachers, and students, and establishing health committees within schools and communities dedicated to facilitating the effective execution of the School Health Programme.